2014
DOI: 10.2217/nnm.14.51
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasmall Superparamagnetic Iron Oxide Nanoparticles Coated with Fucoidan for Molecular MRI of Intraluminal Thrombus

Abstract: In vivo thrombi can thus be evidenced by MRI with USPIO-FUCO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
74
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(75 citation statements)
references
References 48 publications
1
74
0
Order By: Relevance
“…Reduced RECA-1 expression indicated that the sinusoidal lining had largely disappeared. CD34 has been used to detect sinusoidal capillary formation in liver tissue and to differentiate between normal and altered sinusoidal epithelium (20)(21)(22)(23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reduced RECA-1 expression indicated that the sinusoidal lining had largely disappeared. CD34 has been used to detect sinusoidal capillary formation in liver tissue and to differentiate between normal and altered sinusoidal epithelium (20)(21)(22)(23).…”
Section: Discussionmentioning
confidence: 99%
“…Platelet aggregation was assessed by immunohistochemical staining of liver tissues with antibodies to platelet glycoprotein IIb (CD41) (1:100, orb4832; Biorbyt, Cambridge, UK) and P-selectin (1:50, ERP1444(2)(B); Abcam, Tokyo, Japan), the latter being a member of the selectin family of adhesion molecules expressed on activated platelets and endothelium (20). Damage to sinusoidal endothelial cells was determined by immunostaining rat liver tissues with antibodies to rat endothelial cell antigen-1 (RECA-1) (#MCZ-970R; Serotec, Oxford, UK) and CD34 (1:20, AF4117; R&D Systems, Inc., Minneapolis, MN, USA), the latter being a marker of sinusoidal capillary formation in liver tissue, thereby differentiating between normal and altered sinusoidal epithelium (21)(22)(23)(24).…”
Section: Methodsmentioning
confidence: 99%
“…A variety of particles have been reported in the literature for thrombosis detection. [4][5][6][7][8][9][10][11][12][13][14][15][16][17] Compared with ultrasound, [4][5][6][7][8] nuclear medicine, 9,10,18 and computed tomography (CT), 11 the advantages of magnetic resonance imaging (MRI) that are particularly relevant in the context of cardiovascular diseases are its high temporal and spatial imaging resolution, high soft tissue contrast,…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, MR contrast agents, such as gadolinium diethylenetriaminepentaacetic acid (Gd-DTPA), superparamagnetic iron oxide (SPIO), and ultra-small superparamagnetic particles of iron oxide (USPIOs), have been successfully encapsulated into macromolecular polymer particles to create novel contrast agents. [12][13][14][15][16][17] The fibrin-targeted MR molecular probe EP-2104R has entered clinical trials with encouraging results. 19 Comparatively Gd-DTPA, SPIO and USPIO have the advantages of long half-lives, high relaxation rates, and minimal side effects.…”
mentioning
confidence: 99%
See 1 more Smart Citation